2020
DOI: 10.1177/1471301220929534
|View full text |Cite
|
Sign up to set email alerts
|

The use of everyday technologies to enhance well-being and enjoyment for people living with dementia: A systematic literature review and narrative synthesis

Abstract: Background Everyday technologies, such as laptops and tablets, are often used for enjoyment, pleasure, leisure and social participation. Despite this, whilst considerable research has investigated exploring people’s experiences of using assistive technologies, it is not clear how everyday technologies are experienced by individuals living with dementia. The aims of this review were to explore the experiences and views of people living with dementia and carers about using everyday technology to enhance their we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
(139 reference statements)
1
14
0
Order By: Relevance
“…15,16 Finally, off-the-shelf digital Gaming Technology (GT), which supports interactive electronic games such as tablets or motion sensor exergaming devices (e.g. Nintendo Wii and Microsoft Kinect) can provide opportunities for people with dementia and their carers to participate in new leisure experiences that are potentially stimulating and enjoyable 11,17 as well as enable them to master new and sometimes complex skills, increasing their perceived selfconfidence. 18,19 Despite these benefits, people with dementia and their carers face multiple barriers to engaging with these technologies, thereby inhibiting their abilities and rights to participate fully in society.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Finally, off-the-shelf digital Gaming Technology (GT), which supports interactive electronic games such as tablets or motion sensor exergaming devices (e.g. Nintendo Wii and Microsoft Kinect) can provide opportunities for people with dementia and their carers to participate in new leisure experiences that are potentially stimulating and enjoyable 11,17 as well as enable them to master new and sometimes complex skills, increasing their perceived selfconfidence. 18,19 Despite these benefits, people with dementia and their carers face multiple barriers to engaging with these technologies, thereby inhibiting their abilities and rights to participate fully in society.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have highlighted how these devices are being incorporated into dementia care practice as a means to provide activities that are stimulating and enjoyable, and have also noted other benefits for people’s well-being ( Bowes et al, 2018 ; Dove and Astell, 2017 ; Goodall, Taraldsen and Serrano, 2021 ; Joddrell and Astell, 2016 ). Specific positive outcomes for people with dementia (evidence to date relates mostly, but not exclusively to community-dwelling people), include opportunities for: promoting cognitive stimulation, mild physical exercise and social interaction; continuing life-long learning; mastering new and sometimes complex skills; and (re)engaging with meaningful and enjoyable activities that can foster self-confidence by challenging people’s perceptions of their own capabilities ( Cutler, Hicks and Innes, 2016 ; Hicks, Innes and Nyman, 2020 ; Sweeney, Clarke and Wolverson, 2021 ). Furthermore, the ubiquity of these devices throughout society ensures they are more readily accessible and potentially less stigmatised than dementia-specific technology ( Meiland et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We included keywords that were used in related papers (e.g. reviews, studies) about arts and/or technology ( Creech, 2019 ; Fancourt et al, 2021 ; Sweeney et al, 2021 ; Wang et al, 2020 ), keywords identified in key publications and discussions with researchers, and the Arts and Humanities Research Council report “Understanding the value of arts and culture: The AHRC Cultural Value Project” (see Table 1 ). The objective was to be highly inclusive in definition of arts, technology and dementia, before trimming down the selection of articles as a next step.…”
Section: Methodsmentioning
confidence: 99%
“…The increasing “technification” of older adulthood, i.e. the increasing policies, funding and research aimed at innovating technology solutions to the needs of older adults ( Peine, 2019 ) and growing engagement with everyday computer, smartphone and tablet devices for accessing photos and music online ( Sweeney et al, 2021 ) indicates higher technology use in the future. This is notwithstanding the impact of the recent COVID-19 pandemic in accelerating the use of digital strategies through telemedicine ( Cuffaro et al, 2020 ) or arts practices for people living with dementia ( Cutler, 2020 ; Dowson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%